Linear Precoding in Wireless Networks with Channel State Information Feedback - Ahmed, Medra (My University, 2015)
This thesis focuses on the design of linear precoding schemes for downlink multiple-input multiple-output (MIMO) networks. These schemes are designed to be amenable to implementation in wireless networks that allow rate-limited feedback of channel state information (CSI). In the first half of this thesis, memoryless quantization codebooks are designed and incremental vector quantization techniques are developed for the representation of CSI in MIMO point-to-point links and isolated (single-cell) downlink networks. The second half of the thesis seeks to design linear precoding schemes for the multi-cell downlink networks that can achieve improved performance without requiring significantly more communication resources for CSI feedback than those required in the case of an isolated single-cell. For the quantization problem, smooth optimization algorithms are developed for the design of codebooks that possess attractive features that facilitate their implementation in practice in the addition to having good quantization properties. As one example, the proposed approach is used to design rank-2 codebooks that have a nested structure and elements from a phase-shift keying (PSK) alphabet. The designed codebooks have larger minimum distances than some existing codebooks, and provide tangible performance gains. To take advantage of temporal correlation that may exist in the wireless channel, an incremental approach to the Grassmannian quantization problem is proposed. This approach leverages existing codebooks for memoryless quantization schemes and employs a quantized form of geodesic interpolation. Two schemes that implement the principles of the proposed approach are presented. A distinguishing feature of the proposed approach is that the direction of the geodesic interpolation is specified implicitly using a point in a conventional codebook. As a result, the approach has an inherent ability to recover autonomously from errors in the feedback path. In addition to the development of the Grassmannian quantization techniques and codebooks, this thesis studies linear precoder design for the downlink MIMO networks in the cases of small networks of arbitrary topology and unbounded networks that have typical architectures. In particular, a linear precoding scheme for the isolated 2-cell network that achieves the optimal spatial degrees of freedom of the network is proposed. The implementation of a limited feedback model for the proposed linear precoding scheme is developed as well. Based on insight from that model, other linear precoding schemes that can be implemented in larger networks, but with finite size, are developed. For unbounded networks of typical architecture, such as the hexagonal arrangement of cells, linear precoding schemes that exploit the partial connectivity of the network are presented under a class of precoding schemes that is referred to as spatial reuse precoding. These precoding schemes provide substantial gains in the achievable rates of users in the network, and require only local feedback.
Keywords: Wireless Networks; Interference Alignment; Degrees of Freedom; Downlink; Incremental Feedback; Grassmannian; Spatial Reuse Precoding; Fractional